Unemployment in Pontianak City: Macroeconomic Determination - Achmad Achmad (JURNAL MUAMALAT INDONESIA - JMI, 2023)
The purpose of this research is to analyze the influence of investment and population on the unemployment rate in the city of Pontianak. The data used is time series data for ten years from 2006 to 2015. The data analysis technique used is multiple linear regression. The results of this study show that first: the investment variable has no significant effect on the unemployment variable with a Sig value of 0.091. Second: the population variable has a significant edddffect on the unemployment variable with a Sig value of 0.037. Investment and population have a strong relationship with unemployment, which is 76%. The amount of investment and population will have an impact on the level of unemployment.